Budidaya Anggrek Tanah di Desa Pagerharjo, Kecamatan Samigaluh, Kabupaten Kulon Progo - Neni Pancawati; Agusta Ika Prihanti Nugraheni; Nova Perwira Yuda (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2019)
Pegerharjo Village is a Development Village of the Management Study Program of the Department of Economics and Business, UGM Vocational School. This village is a tourist village with local contents, the implementation of which is carried out by the community, especially by the Working Group of mothers, and Karang Taruna. This area is known as the tourist village called Nglinggo Tourism Village. Pagerharjo Village also has plans to develop and develop other village tourism objects to be carried out in 10 locations supported by the stipulation of the Pagerharjo Village Regulation No. 6 of 2017 concerning Review of Pagerharjo Village Medium Term Development Plan for 2014-2019. The development and development of tourism objects in Pagerharjo Village is expected to be able to increase competitiveness and attract more tourists in accordance with the carrying capacity they have. One of the problems faced is how to increase economic empowerment through land use to support tourism development in Pagerharjo Village. It will be endeavored by developing the Nglinggo tourist village, equipped with Rest Area and a place where you can select or display photos. The Segitik Rest area is one of the development locations located in the Tanah Kas Desa which is an asset of the government of the Pagerharjo Village. The location will be developed to become the center of the people's economy to support the development of Nglinggo Tourism Village. The dedication team will assist Pagerharjo Village with training in the cultivation of soil orchids / slices and support the development of tourism in Pagerharjo Village. The orchid cultivation is planted and developed in the rest area of Segitik to become an orchid garden. The community and the Government of Pagerharjo Village are very supportive and enthusiastic in participating in the training and mentoring